Enhancing Hotel Room Bookings through Instagram Marketing - Riza Zalzabilah Hadi Syahputri; Muhammad Arfin Muhammad Salim; Islahuddin (Journal of Economic Education and Entrepreneurship Studies, 2024)
Tourism is a vital sector globally, encompassing travel, leisure, and associated industries that significantly bolster economies, especially in developed nations. Indonesia's tourism potential holds promise for economic growth through increased visitor numbers and new destination developments. The hotel industry, a cornerstone of global tourism, adapts to technological advancements and shifting consumer behaviors to maintain competitiveness. This study investigates the efficacy of Instagram as a digital marketing tool in enhancing hotel room bookings, focusing on Whiz Prime Hotel Sudirman Makassar. Methods included direct observation, engagement analysis, and stakeholder interviews. The findings underscore Instagram's pivotal role in showcasing hotel amenities, promotions, and exclusive offers to a global audience, thereby fostering direct engagement and influencing booking decisions. Effective strategies and challenges in leveraging Instagram were identified, highlighting the importance of innovative content, real-time responsiveness, and adaptation to digital trends. Despite challenges such as market saturation and evolving consumer preferences, proactive measures like enhancing content quality and collaborating with influencers can amplify Instagram's impact on room sales. Recommendations include continuous staff training, strategic partnerships, and analytics utilization to optimize marketing efforts and sustain growth in the competitive digital tourism landscape. This study contributes insights into leveraging Instagram for hotel marketing, emphasizing its role in driving profitability and enhancing brand visibility within the dynamic hospitality sector.